Sudden, unexpected death of a 15-year-old boy due to pancarditis: A case report and possible etiopathogenesis. Issue 35 (August 2016) - Osculati, Antonio; Visonà, Silvia Damiana; Ventura, Francesco; Castelli, Francesca; Andrello, Luisa
Abstract: Background: Generally, rheumatic heart disease is, today, sporadic in developed countries, even though it continues to be a major health hazard in the developing ones. It is also a very rare cause of sudden unexpected death. We report a case of a 15-year-old boy who suddenly died at home. Since 3 days he had presented fever and chest pain. The family physician had diagnosed bronchitis and treated the boy with amoxicillin. Methods: Seven hours after death, a forensic autopsy were performed . Before the autopsy, anamnesis and some circumstantial data were collected from the boy's parents. During the autopsy, samples for histological, toxicological and molecular examinations were collected. The samples for the histology (brain, hypophysis, heart and pericardium, lungs, spleen, liver, kidney, adrenal glands) were formalin fixed and paraffin embedded. Each section was stained with Hematoxylin-Eosin. Immunostaining was also performed, with anti-CD 68, anti-CD3, anti-CD 20, anti-myeloperoxidase. Microbiological cultures were performed on cardiac blood, myocardium, pericardial effusion and cerebrospinal fluid samples collected during autopsy. Blood specimens were also processed through PCR, in order to reveal the presence of Enteroviruses, Chickenpox virus, Epstein Barr virus. Also chemical-toxicological examinations for the detection of the main medications and drugs were performed on blood samples. Results: The anamnesis, collected before the autopsy, revealed an acute pharyngitis few weeks before. The autopsy, and the following histological and immunochemical examinations suggested an immunological etiology. The immunohistochemistry, showing a strong positivity of antiCD68 antibodies, integrated with clinical-anamnestic information, leads to hypothesize a rheumatic carditis. Conclusion: In light of this case, at least 3 main messages of great importance for the clinician can be deduced. First, an accurate anamnesis collected by the family physician could have led to the correct interpretation of the objective signs and the administration of an appropriate therapy. Second, a pharyngeal swab should be performed for cases involving sore throat in young children and adolescents, especially in cases involving repeated pharyngitis. Finally, apparently unremarkable findings revealed from objective examinations can be signs of a serious disease. Moreover, in some cases, these diseases can be lethal if they are not properly treated.